Deciphering the Translation Initiation Factor 5A Modification Pathway in Halophilic Archaea. (8th December 2016) - Prunetti, Laurence; Graf, Michael; Blaby, Ian K.; Peil, Lauri; Makkay, Andrea M.; Starosta, Agata L.; Papke, R. Thane; Oshima, Tairo; Wilson, Daniel N.; de Crécy-Lagard, Valérie
Abstract : Translation initiation factor 5A (IF5A) is essential and highly conserved in Eukarya (eIF5A) and Archaea (aIF5A). The activity of IF5A requires hypusine, a posttranslational modification synthesized in Eukarya from the polyamine precursor spermidine. Intracellular polyamine analyses revealed that agmatine and cadaverine were the main polyamines produced in Haloferax volcanii in minimal medium, raising the question of how hypusine is synthesized in this halophilic Archaea. Metabolic reconstruction led to a tentative picture of polyamine metabolism and aIF5A modification in Hfx. volcanii that was experimentally tested. Analysis of aIF5A from Hfx. volcanii by LC-MS/MS revealed it was exclusively deoxyhypusinylated. Genetic studies confirmed the role of the predicted arginine decarboxylase gene (HVO_1958) in agmatine synthesis. The agmatinase-like gene (HVO_2299) was found to be essential, consistent with a role in aIF5A modification predicted by physical clustering evidence. Recombinant deoxyhypusine synthase (DHS) from S. cerevisiae was shown to transfer 4-aminobutyl moiety from spermidine to aIF5A from Hfx. volcanii in vitro. However, at least under conditions tested, this transfer was not observed with the Hfx. volcanii DHS. Furthermore, the growth of Hfx. volcanii was not inhibited by the classical DHS inhibitor GC7. We propose a model of deoxyhypusine synthesis in Hfx. volcanii that differs from the canonical eukaryotic pathway, paving the way for further studies.